Drag me to hell - Raimi, Sam.; Lohman, Alison, 1979-; Long, Justin, 1978-; Raver, Lorna (Universal City, CA : Universal Studios Home Entertainment, 2009)
To secure a promotion, loan officer Christine evicts an old woman and becomes the recipient of a particularly nasty curse.
"Unrated director's cut"--Container.
Originally released as a motion picture in 2009.
Features: theatrical version of film (rated PG-13), Production video diaries : the bloody nose; inside the psychic world; makeup effects; "Alison in mud" featurette; "Wirework and nightmare" featurette; Justin Long profile; "The parking lot fight" featurette; "The goat" featurette; "Set tour : the great room" featurette; "Puzzle car" featurette; "Dragging her to hell" featurette; sound design featurette.
Alison Lohman, Justin Long, Lorna Raver, Dileep Rao, David Paymer.
MPAA rating: Not rated.
DVD, Dolby digital 5.1.
Keywords: Blessing and cursing -- Drama; Loan officers -- California -- Los Angeles -- Drama; Repossession -- California -- Los Angeles -- Drama; Horror films; Video recordings for the hearing impaired; Fiction films; Feature films